Effect and molecular mechanism of mTOR inhibitor rapamycin on temozolomide-induced autophagic death of U251 glioma cells - Li, Bing (Oncol Lett, 2018)
Glioma is a malignant tumor of the glial tissue that is difficult to excise through surgery, with poor patient prognosis. The use of chemotherapeutic drugs alone to treat glioma following surgery results in a high probability of sequelae, such as tumor recurrence. The present study investigated the effects of a novel treatment combination on glioma cells and determined the molecular mechanisms underlying its action. The effect of temozolomide (TMZ) combined with rapamycin (RAPA) on the TMZ-induced autophagic death of U251 glioma cells was examined. The U251 cell line was treated with TMZ combined with RAPA, and the cell survival rate and half maximal inhibitory concentration (IC(50)) of TMZ/RAPA was detected using the Cell Counting Kit-8 (CCK-8) assay. Flow cytometry was used to detect changes in cell cycle distribution. The formation of acidic vesicular organelles (AVOs) in the cytoplasm was identified using fluorescence microscopy and quantitatively analyzed. Western blotting was performed to detect the expression levels of autophagy-associated proteins Beclin-1 and microtubule associated protein 1 light chain 3 alpha (MAP1LC3A)-I and II. RAPA (1.25 nM) combined with 5 µM TMZ markedly inhibited U251 cell growth. RAPA reinforced TMZ-induced autophagic death, reducing the IC(50) value of treatment when combined (TMZ alone, 22.5±3.23 µM vs. TMZ and RAPA, 10.35±2.81 µM). Compared with the control group, the proportion of cells in G(2)/M were markedly increased following treatment with TMZ combined with RAPA. Acridine orange staining demonstrated that TMZ combined with RAPA could markedly enhance the generation of intracellular AVOs compared with TMZ or RAPA alone. In addition, Beclin-1 and LC3-II protein expression was markedly increased compared with the control and single treatment groups (P<0.05). The results of the present study indicate that RAPA reinforces TMZ-induced autophagic death of U251 glioma cells, providing a novel therapeutic combination for the treatment of malignant glioma.